Shaping “Reach Out, Build Up, Send Back”: Overseas Christian Fellowship’s Student Returnee Mission and Cold War Australia’s Colombo Plan, 1959–1979 - Sim, Joshua Dao Wei (Social sciences and missions, 2024)
Why did Asian Christian international students return home with a missionary mindset during the Cold War? This study answers the question by investigating Overseas Christian Fellowship (OCF) Australia and its student returnee mission. I show that OCF’s returnee mission was shaped by Australia’s Cold War foreign policy – the Colombo Plan Scheme. The paper argues that the time-limited conditions imposed by the Scheme established a migratory and educational training pattern which influenced OCF’s mission of evangelising overseas students and training its members to return home as Christian witnesses. In conclusion, I observe a student-led, faith-based Australia-Asia imaginary emerging from OCF’s mission.